Religion and spirituality in chronic illnesses: a case study of three living related kidney transplant recipients - Ismail, Nik Ahmad Hisham; Fong, Chan Kwai (Institut Terjemahan dan Buku Malaysia, 2016)
The role of religion and spirituality in the care of people suffering from chronic illnesses. The effects of religion and spirituality on patient;s treatment options and patients' perceptions toward religion and spirituality.